Results of multicenter registry for patients with inherited factor VII deficiency in Turkey - Akdeniz, Aydan; Unuvar, Aysegul; Ar, Muhlis Cem; Pekpak, Esra; Akyay, Arzu; Mehtap, Ozgur; Demir, Ahmet Muzaffer (Taylor & Francis Ltd, 2022)
Introduction: Inherited factor VII (FVII) deficiency (FVIID) is the most common of inherited rare bleeding disorders. Other determinants of clinical severity apart from FVII level (FVIIL) include genetic and environmental factors. We aimed to identify the cut-off FVIILs for general and severe bleedings in patients with FVIID by using an online national registry system including clinical, laboratory, and demographic characteristics of patients. Methods: Demographic, clinical, and laboratory data of patients with FVIID extracted from the national database, constituted by the Turkish Society of Hematology, were examined. Bleeding phenotypes, general characteristics, and laboratory features were assessed in terms of FVIILs. Bleeding rates and prophylaxis during special procedures/interventions were also recorded. Results: Data from 197 patients showed that 46.2% of patients had FVIIL< 10%. Most bleeds were of mucosal origin (67.7%), and severe bleeds tended to occur in younger patients (median age: 15 (IQR:6-29)). Cut-off FVIILs for all and severe bleeds were 16.5% and 7.5%, respectively. The major reason for long-term prophylaxis was observed as central nervous system bleeding (80%). Conclusion: Our data are consistent with most of the published literature in terms of cut-off FVIIL for bleeding, as well as reasons for prophylaxis, showing both an increased severity of bleeding and younger age at diagnosis with decreasing FVIIL. However, in order to offer a classification similar to that in Hemophilia A or B, data of a larger cohort with information about environmental and genetic factors are required.
Keywords: Factor VII; rare diseases; FVII deficiency; hemorrhage; blood coagulation disorder